Effects of Caffeine Ingestion on Anaerobic Capacity in a Single Supramaximal Cycling Test - Miyagi, Willian E.; Bertuzzi, Romulo C.; Nakamura, Fabio Y.; de Poli, Rodrigo A. B.; Zagatto, Alessandro M. (Frontiers in Nutrition, 2018)
The aim of this study was to verify the effects of caffeine on anaerobic capacity estimated by the sum of the estimated glycolytic [E[La]] and phosphagen [EPCr] metabolism based on blood lactate and excess post-oxygen consumption responses (AC[La−]+EPOCfast). Fourteen male cyclists were submitted to a graded exercise test to determine the maximal oxygen uptake (V°O2max) and intensity associated with V°O2max (iV°O2max). Subsequently, the participants performed two supramaximal efforts at 115% of iV°O2max to determine the AC[La−]+EPOCfast, after previous supplementation with caffeine (6 mg·kg−1) or a placebo (dextrose), in a cross over, randomized, double blind, and placebo-controlled design. The time to exhaustion was higher in the caffeine (186.6 ± 29.8 s) than in the placebo condition (173.3 ± 25.3 s) (p = 0.006) and a significant correlation was found between them (r = 0.86; P = 0.00008). Significant differences were not found between AC[La−]+EPOCfast values from the placebo (4.06 ± 0.83 L and 55.2 ± 5.7 mL·kg−1) and caffeine condition (4.00 ± 0.76 L and 54.6 ± 5.4 mL·kg−1); however, a significant correlation was observed only for AC[La−]+EPOCfast expressed in absolute values (r = 0.74; p < 0.002). The E[La] and EPCr also presented no significant differences and they were significantly correlated (r = 0.82 and r = 0.55, respectively; p < 0.05). We conclude based on the overall comparison of mean values between two treatments that acute caffeine ingestion improves the time to exhaustion but does not affect anaerobic capacity estimation.